Respiratory Medicine and Science - Pokorski, Mieczyslaw (Neuroscience and Respiration, 2016)
This is the book that provides expert advice on the clinical aspects of respiratory disorders. The exemplary topics are obstructive sleep apnea, chronic obstructive pulmonary disease, angiological sequelae of sarcoidosis, or epidemiology of seasonal influenza epidemics. The emphasis is placed on the pathogenetic aspects, and the relevance and translational potential of experimental studies. The book also presents the latest trends having to with more accessible and personalized health care for chronically ill aged persons, stressing the importance of the mental and emotional sphere in upholding the feeling of life satisfaction. The entwinement of pathophysiological processes raises the issue of the development of individualized and targeted therapeutic management strategies. Clinical practitioners should liaise with medical researchers on the design and execution of investigations to enhance translational power of basic science findings. The book will be of interest to clinicians, researchers, health care providers, and other medical professionals.